A Technique Of Scan Blindness Elimination For Planar Phased Array Antenna Using Miniaturized EBG - Mohamad Isa, Mohd Sa'ari; Langley, Joe; Khamas, S; Mohd Zin, Mohd Shahril Izuan; Zakaria, Zahriladha; Haron, Nor Zaidi; Ahmad, Azhar (Penerbit UTM Press, 2014)
-